Efeitos anti-inflamatórios e antirreabsortivo ósseo da minociclina na doença periodontal induzida em ratos diabéticos e normais - Menezes, Silvana Magalhães Siqueira (2012)
The immune/inflammatory response has a key role in the periodontal disease (DP) whose progression results from an imbalance between periodontopathogenic microorganisms and the host response. This leads to the production and release of inflammatory mediators and tissue damage. DP is considered the sixth complication in diabetes. Furthermore, diabetes mellitus and periodontitis present common links related to inflammation processes and immunologic system stimuli and, in the presence of diabetes with uncontrolled insulin levels, the aggravation of preexistant periodontitis may occur. Also, DP may reciprocally aggravate the diabetic state. Minocycline (M) is a second generation tetracycline showing anti-inflammatory effects independent of its antimicrobial action. The objectives of the present work were to investigate the effects of M (25 and 50 mg/kg, p.o.) in an experimental model of periodontal disease (DPE), in the presence and absence of alloxan-induced diabetes (DIA) in rats. DPE was induced through a nylon thread insertion and ligation in the second superior molar of male Wistar rats (200 g).For histological analyses and measurements of biochemical parameters, as glycemia, cholesterol, triglycerides and liver transaminases (ALT and AST) the groups (n=6) were divided : DPE; DPE+DIA; DPE+M25; DPE+M50; DPE+DIA+M25 and DPE+DIA+M50. After 11 or 30 days the animals were sacrificed. . Immunohitochemistry for TNF-α, iNOS and MMP-9 was performed in groups (n=4): DPE; DPE+DIA; DPE+M50; and DPE+DIA+M50. After 11 days the animals were sacrificed. The results showed that M50 presents a potent anti-inflammatory activity, preserving the alveolar and cement bones in the DPE and DPE+DIA models, after both periods of time. Under these experimental conditions, M50 also significantly reduced blood glucose levels. Furthermore, M50 reduced imunnostainings for TNF-α, iNOS and MMP-9. M25 did not significantly reduce the inflammatory process in DPE animals sacrificed at the 11th day after DPE induction.In addition, levels of triglycerides and total cholesterol were reduced in the DPE model, in the presence and absence of diabetes, after M25 and M50 treatments. Our data demonstrated that minocycline at both doses was well tolerated, and no significant alterations in ALT levels were observed in the DPE and DPE+DIA groups, at the 11th and 30th day, as well as on the levels of AST in groups DPE (11th day). However, the DPE + DIA group treated with M50 for 30 days presented a significant increase in AST levels. Our results strongly suggest that minocycline could be used for the periodontal disease treatment, since it protects the periodontium and reduces glycemia levels in the presence of the diabetic state. These beneficial effects are probably related to the potent anti-inflammatory properties of this drug, point out to its potential as an alternative for the treatment of diseases where the inflammatory process play a key role.